Uncovering The Traces Of Freijer's Compendium: Historical Analysis And Its Role In Islamic Marriage Law In Indonesia - Aulal Musyafiul Aliya Dewi; Nurwanti Nurwanti (Jember: Sharia Faculty State Islamic University of Kiai Haji Achmad Siddiq Jember, 2024)
The purpose of this study is to identify the role of the Freijer Compendium on marriage law in Indonesia. This research method uses normative legal research (doctrinal), a library research aimed at written regulations. In this case, it focuses on the main source, namely the Freijer Compendium manuscript, as well as literature related to marriage law in Indonesia. The results show that the Freijer’s Compendium influenced marriage law in Indonesia which is an integral part of fundamental human rights, because legal recognition and protection of the institution of marriage is essential in upholding the principles of equality and justice in society. Freijer's Compendium then shaped the general understanding of Islamic marriage and inheritance law in Indonesia and became the legal basis for the Ordonnantie op het Huwelijk van Inlanders (Bumiputera Marriage Ordinance) during the Dutch government which developed into the formation of Law No. 1 of 1974.